Answer
Here are the factored forms of the given expressions:
1. \( a^{3} - 27 = (a - 3)(a^{2} + 3a + 9) \)
2. \( 27p^{3} - 8q^{3} = (3p - 2q)(9p^{2} + 6pq + 4q^{2}) \)
3. \( -125 + p^{3} = (p - 5)(p^{2} + 5p + 25) \)
4. \( x^{6} - y^{6} = (x - y)(x + y)(x^{2} + xy + y^{2})(x^{2} - xy + y^{2}) \)
5. \( \frac{x^{3}}{8} + \frac{64}{y^{3}} = \left(\frac{x}{2} + \frac{4}{y}\right)\left(\frac{x^{2}}{4} - \frac{2x}{y} + \frac{16}{y^{2}}\right) \)
Solution
Sure, let's factor each of the given expressions step by step.
---
### (3) \( a^{3} - 27 \)
This is a **difference of cubes** since \( 27 = 3^3 \).
\[
a^{3} - 3^{3} = (a - 3)(a^{2} + 3a + 9)
\]
**Factored Form:**
\[
a^{3} - 27 = (a - 3)(a^{2} + 3a + 9)
\]
---
### (6) \( 27p^{3} - 8q^{3} \)
This is also a **difference of cubes** where \( 27p^{3} = (3p)^3 \) and \( 8q^{3} = (2q)^3 \).
\[
(3p)^{3} - (2q)^{3} = (3p - 2q)\left[(3p)^2 + 3p \cdot 2q + (2q)^2\right]
\]
\[
= (3p - 2q)(9p^{2} + 6pq + 4q^{2})
\]
**Factored Form:**
\[
27p^{3} - 8q^{3} = (3p - 2q)(9p^{2} + 6pq + 4q^{2})
\]
---
### (9) \( -125 + p^{3} \)
Rewrite the expression to identify it as a **difference of cubes**. Note that \( -125 = (-5)^3 \).
\[
p^{3} - 5^{3} = (p - 5)\left[p^{2} + 5p + 25\right]
\]
**Factored Form:**
\[
-125 + p^{3} = (p - 5)(p^{2} + 5p + 25)
\]
---
### (12)* \( x^{6} - y^{6} \) *(Careful!)*
This expression is a **difference of squares**, which can be further factored into a product of **difference and sum of cubes**.
1. **First, apply the difference of squares:**
\[
x^{6} - y^{6} = (x^{3})^{2} - (y^{3})^{2} = (x^{3} - y^{3})(x^{3} + y^{3})
\]
2. **Now, factor each part using the difference and sum of cubes formulas:**
\[
x^{3} - y^{3} = (x - y)(x^{2} + xy + y^{2})
\]
\[
x^{3} + y^{3} = (x + y)(x^{2} - xy + y^{2})
\]
3. **Combine all factors:**
\[
x^{6} - y^{6} = (x - y)(x + y)(x^{2} + xy + y^{2})(x^{2} - xy + y^{2})
\]
**Factored Form:**
\[
x^{6} - y^{6} = (x - y)(x + y)(x^{2} + xy + y^{2})(x^{2} - xy + y^{2})
\]
---
### (15) \( \frac{x^{3}}{8} + \frac{64}{y^{3}} \)
First, rewrite the expression to recognize it as a **sum of cubes**:
\[
\frac{x^{3}}{8} + \frac{64}{y^{3}} = \left(\frac{x}{2}\right)^{3} + \left(\frac{4}{y}\right)^{3}
\]
Now, apply the sum of cubes formula:
\[
a^{3} + b^{3} = (a + b)(a^{2} - ab + b^{2})
\]
Here, \( a = \frac{x}{2} \) and \( b = \frac{4}{y} \):
\[
\left(\frac{x}{2} + \frac{4}{y}\right)\left(\left(\frac{x}{2}\right)^{2} - \frac{x}{2} \cdot \frac{4}{y} + \left(\frac{4}{y}\right)^{2}\right)
\]
Simplify inside the parentheses:
\[
= \left(\frac{x}{2} + \frac{4}{y}\right)\left(\frac{x^{2}}{4} - \frac{2x}{y} + \frac{16}{y^{2}}\right)
\]
**Factored Form:**
\[
\frac{x^{3}}{8} + \frac{64}{y^{3}} = \left(\frac{x}{2} + \frac{4}{y}\right)\left(\frac{x^{2}}{4} - \frac{2x}{y} + \frac{16}{y^{2}}\right)
\]
---
Feel free to reach out if you need further clarification on any of these factorizations!
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution